DIDACTIC SUPPORT FOR THE DEVELOPMENT OF ELECTRONIC EDUCATIONAL RESOURCES BASED ON PROBLEM-BASED APPROACHES - Aygul Kaldibaeva Jaqsiliqovna (American Journals, 2025)
The integration of problem-based learning (PBL) with electronic educational resources (EERs) holds transformative potential for modern education, fostering active, student-centered learning. This study investigates the didactic principles necessary for developing EERs tailored to PBL, focusing on their alignment with learning objectives, interactivity, scaffolding, collaboration, and accessibility. A mixed-methods approach was employed, combining a systematic literature review, case study analysis, and the development of a comprehensive framework for EER design and implementation in PBL settings. The findings provide actionable insights for educators and institutions, addressing challenges and opportunities in leveraging digital tools to optimize learning outcomes across diverse educational contexts.
Keywords: Pedagogical skill, didactic support, electronic educational resources, problem-based approaches, modern education.